Centering intersectional breast cancer screening experiences among black, Latina, and white women: a qualitative analysis - Ruiz, Sienna; Abdur-Rashid, Kamilah; Mintz, Rachel L.; Britton, Maggie; Baumann, Ana A.; Colditz, Graham A.; Housten, Ashley J. (Frontiers in Public Health, 2024)
ObjectiveMammography screening guidelines in the United States highlight the importance of informing and involving women when making their breast cancer screening decisions. However, the complexity of interpreting and applying these population-level guidelines can contribute to patient burden. Patient-centered communication strategies can alleviate patient burden, but few consider perspectives from racially and ethnically marginalized populations. We examine diverse women’s perspectives on screening to characterize patient-centered experiences.MethodsWe conducted 28 focus groups with 134 non-Latina Black (n = 51), non-Latina White (n = 39), and Latina (n = 44) participants. We coded participants’ discussion of their screening influences. We used deductive and inductive qualitative methods to identify common themes.ResultsWe identified three themes: (1) personal relationships with primary care providers, (2) potential impacts of cancer on families, and (3) interactions with medical systems. Most White participants described trusting physician relationships in contrast to perfunctory, surface-level relationships experienced by many Black participants; high costs of care prevented many Latina participants from accessing care (Theme 1). Diagnosis was a concern for most Black participants as it could burden family and most Latina participants as it could prevent them from maintaining family well-being (Theme 2). While many White participants had general ease in accessing and navigating healthcare, Latina participants were often held back by embarrassment—and Black participants frequently described disrespectful providers, false negatives, and unnecessary pain (Theme 3).ConclusionCultural and structural factors appeared to influence participants’ approaches to breast cancer screening. Structural barriers may counteract culturally salient beliefs, especially among Black and Latina participants. We suggest patient-centered communication interventions be culturally adjusted and paired with structural changes (e.g., policy, insurance coverage, material resources) to reflect women’s nuanced values and intersectional social contexts.